Efeitos de uma intervenção na visão periférica e no tempo de reação sobre o desempenho tático/técnico de praticantes de futebol - Silva, Diozer Dalmolin da (2018)
In soccer, it is possible to notice that players must be able to act tactically and consciously in the face of the problem situations that the game presents and that this implies good cognitive, motor and perceptive conditions. The soccer player, to get a good performance, should be able to perceive all relevant information of the situation in order to properly decide which the correct motor gesture to perform. Therefore, the study shows two perceptive-motor abilities important for soccer, Reaction Time (TR) and Peripheral Vision (PV). In this way, the research aimed to analyze the effects of a proposal of intervention in the VP and in the TR on the tactical / technical performance in the soccer modality, in youth teams and school practitioners. To achieve the stated objectives, the study had two main focuses. One of them concerns the structuring process of the intervention program, it was established the contextualization on the subject within the context of the variables studied, along with that the organization of the intervention program. As a second focus, we analyzed the effects that the intervention program had after its application in individuals. Thus, 28 subjects in the age range of 15 to 16 years old were divided into two groups, an Experimental Group (EG) consisting of 16 soccer practitioners from Sociedade Esportiva Novo Horizonte’s youth team from Santa Maria -RS and school football practitioners from the José Otão High School, also from the same city; a Control Group (CG), made up of 12 subjects from the same institutions. Pre-tests were performed in the groups to measure the TR and VP through the software of the Vienna Test, the performance of the individuals in soccer technical situations was also measured through the Mor-Christian Test Protocol, after which it was carried out a training program with GE only. Finally, a new application of the tests (post-test) were done in both groups to verify and compare the evolutions of the investigated individuals. All descriptive and comparative analyzes were performed using SPSS version 20.0 for Windows, adopting a significance level of 5%. The results showed that the intervention program was effective for improving perceptual-motor skills and for performance skills in soccer.